Risk factors of mortality after surgical correction of ventricular septal defect following myocardial infarction: Retrospective analysis and review of the literature. (1st March 2016) - Cinq-Mars, Alexandre; Voisine, Pierre; Dagenais, François; Charbonneau, Éric; Jacques, Frédéric; Kalavrouziotis, Dimitris; Perron, Jean; Mohammadi, Siamak; Dubois, Michelle; Le Ven, Florent; Poirier, Paul; O'Connor, Kim; et al.
Abstract: Background: Rupture of the ventricular septum following acute myocardial infarction (AMI) is an uncommon but serious complication, usually leading to congestive heart failure and cardiogenic shock. Surgical repair is the only definitive treatment for this condition. Methods: We review our experience of surgical repair of post-infarction ventricular septal defects (VSDs), analyze the associated risk factors and outcomes, and do a complete review of the literature. A retrospective study was performed on 34 consecutive patients who had undergone surgical repair for VSDs following AMI from December 1991 to July 2014. Preoperative, clinical and echocardiographic variables were studied by uni-and multivariate analyses. Results: Mortality was analyzed for the entire group of patients. Mean age was 69 ± 7 years with 44% women. VSDs were anterior in 11 (32%) and posterior in 23 (68%) patients. A majority, 24 (71%) patients were in cardiogenic shock. Median interval from myocardial infarction to VSDs repair was 7 days. The 30 days operative mortality was 65%. Mortality within the posterior VSDs group was 74% and the anterior VSDs group was 46% (P = 0.14). Concomitant coronary artery bypass graft (CABG) did not influence early or late survival. Multivariate analysis identified older age (HR = 1.11, P = 0.0001) and shorter time between AMI and surgery (HR = 0.90, P = 0.015) as independent predictors of 30-day and long-term mortality. Conclusion: In conclusion, surgical repair of post-AMI VSDs carries a high operative mortality. An algorithm of treatment for the management of these patients is suggested.